FAMILY EDUCATION ACCORDING TO LUQMAN AL-HAKIM: A Review of the Tarbawi Interpretation - WAWAN WAHYUDIN (Tazkiya, 2015)
This study aims to (1) describe the concept of Luqman Al-Hakim in family education and (2) describe the main points of the material presented by Luqman Al-Hakim in educating families. The problem of this study is (1) How does the concept of Luqman Al-Hakim in educating families? and (2) What are the main points of the material conveyed by Luqman Al-Hakim in educating families? This research uses qualitative method with content analysis techniques. Review based on Tarbawi Interpretation or educational commentary. The data source of this research are the verses of Qur’an that tells Luqman Al-Hakim in educating families, interpretation of these verses, and stories about Luqman Al-Hakim’s life. The conclusion of this study is what is gained by Luqman from Allah above is the favor of God which is does not seem (by the naked eye), are about knowledge, wisdom (hikmah), and wises in Luqman. Furthermore, Luqman taught faith, worship, and the noble spirit to his son so that he became a servant of the righteous.